Respon Tanaman Kedelai Terhadap Pengayaan Kompos Tandan Kosong Kelapa Sawit Pada Perkebunan Kelapa Sawit Muda Di Lahan Gambut - Sumiati, Sumiati; Nelvia, Nelvia; Adiwirman, Adiwirman (Jurnal Agro Teknologi Tropika, 2016)
The research aims to study the effect of empty fruit bunchesÂ of palm oil compost (EFBPOC) which is enriched with palm oil bunch ash (POBA), palm oil mill effluent (POME), and Trichoderma on the growth and yield of soybean as a crop on the sidelines of the young palm oil plantations in peatlands. The Study Research using randomized block design (RBD) consisting of 6 treatments ie: without EFBPOC; 5 tons/ha EFBPOC; 5 tons/ha EFBPOC + 100 l/ha POME + 0.2 kg/ha of Trichoderma; 5 tons/ha EFBPOC + 0.5 tons/ha OPBA + 100 L/ha POME + 0.2 kg/ha Trichoderma; 5 tons/ha EFBPOC + 1 tons/ha OPBA + 100 L/ha POME + 0.2 kg/ha of Trichoderma; 5 tons / ha EFBPOC + 1.5 tons/ha OPBA + 100 L/ha of POME+ 0.2 kg / ha of Trichoderma and 3 reflications. The data obtained were statistically analyzed using analysis of variance (F test) and continued with DNMRT (Duncan s New Multiple Range Test ) at 5% level. The results showed EFBPOC without enrichment and enriched with 100 l/haÂ POME + 0.2 kg/ha trichoderma and the addition of 0.5 up to 1.5 tons/ha OPBA able to increase plant height, number of primary branches, days to flowering, number of pods, the percentage of pithy pods, seed weight at plot and a dry weight of 100 seeds of soybeans grown on the young oil palm plantations on peatlands, wich all soybeans planted without EFBPOC have dead at 3 month after planted. Giving 5 tons/ha EFBPOC + 1 ton/ha OPBA + 100 l/ha POME + 0.2 kg/ha of Trichoderma provides the highest seed weight is 239.60 g/m2 (2.40 tonnes/ha).